CFD-Based Wind Assessment for Suburban Buildings. The Case Study of Aarhus University, Herning Campus - Strasszer, David; Xydis, George (Frontiers in Energy Research, 2020)
The development in the field of wind turbines is continuously growing. However, most of the times, the energy of wind is exploited by using huge wind-power plants, while wind energy installations in urban and suburban areas, as space and available land, are a lot more limited, is something relatively new, with great potential though. The major challenge regarding small urban wind turbines can be summarized as a lack of understanding of the wind resource in the built environment, with a combination of missing measurements in this field that needed to be addressed. Aarhus University Campus Herning, located in the suburban area of Herning, is looking for a suitable place to install one small wind turbine (SWT). This study attempts to provide a comprehensive framework for SWTs and the characteristics of urban wind flow. The analysis helped in identifying the two most appropriate sites for SWTs installation sites in the AU Herning building